First geochemical and geochronological characterization of late cretaceous mesosilicic magmatism in gastre, Northern patagonia, and its tectonic relation to other coeval volcanic rocks in the region - Zaffarana, Claudia Beatriz (2018)
Fil: Zaffarana, Claudia. Universidad Nacional de Río Negro. Río Negro, Argentina.